The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1530/jrf.0.0980631
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase activity and oestrogen concentrations in bovine cotyledons and caruncles during gestation and parturition

Abstract: Two peaks of aromatase activities were detected in bovine cotyledons, 2.76 +/- 0.96 pmol min-1 mg-1 protein at month five of gestation and 3.62 +/- 0.78 pmol min-1 mg-1 protein immediately after parturition, but aromatase activity in caruncles was very low throughout gestation. Oestrone concentrations in the cotyledons and caruncles were 0.93 +/- 0.50 and 1.51 +/- 0.69 ng mg-1 protein at month five of gestation, but 4.31 +/- 1.66 and 3.36 +/- 0.98 ng mg-1 protein immediately after parturition, indicating a bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
1
17
2
1
Order By: Relevance
“…Staining in placentomes from animals at day 90 and 180 clearly showed higher signal intensity in the trophoblast covering primary villi compared with other parts of the villous tree. Observations in placentomes from a cow after induction of parturition and in a cow at normal term indicates that prepartal up-regulation of aromatase activity (Tsumagari et al 1993) follows a pattern similar to the one identified for P450c17. The up-regulation of P450arom and oestrogen receptor b (Schuler et al 2005) concomitant with TGC differentiation points to an autocrine regulatory role of placental oestrogens during this process in addition to their previously postulated functions as local caruncular growth factor (Schuler et al 2002).…”
Section: Day 90mentioning
confidence: 57%
See 1 more Smart Citation
“…Staining in placentomes from animals at day 90 and 180 clearly showed higher signal intensity in the trophoblast covering primary villi compared with other parts of the villous tree. Observations in placentomes from a cow after induction of parturition and in a cow at normal term indicates that prepartal up-regulation of aromatase activity (Tsumagari et al 1993) follows a pattern similar to the one identified for P450c17. The up-regulation of P450arom and oestrogen receptor b (Schuler et al 2005) concomitant with TGC differentiation points to an autocrine regulatory role of placental oestrogens during this process in addition to their previously postulated functions as local caruncular growth factor (Schuler et al 2002).…”
Section: Day 90mentioning
confidence: 57%
“…In vitro investigations using placental homogenates suggest that, as in the sheep (Mason et al 1989), P450c17 activity in bovine trophoblast is significantly up-regulated at parturition (Schuler et al 1994). Aromatisation in microsomes prepared from bovine cotyledons exhibits a distinct peak in the fifth month of gestation but is low thereafter until the last month of gestation, when it increases again around the time of parturition (Tsumagari et al 1993). Only sporadic, and in part contradictory, information is available on the expression of P450arom on a cellular level in bovine placentomes.…”
Section: Introductionmentioning
confidence: 92%
“…Both oestrone and oestradiol were detected in cotyledonary and caruncular tissues from about the fourth month of gestation (Tsumagari et al, 1993). This suggests that the placenta is able to produce oestrogens from as early as the first trimester.…”
Section: Oestrogen Productionmentioning
confidence: 94%
“…The foetal cotyledon is also the primary site of P450c17 and P450arom localization, the key enzymes for the synthesis of oestrogens (Tsumagari et al, 1993;Schuler et al, 2006a). P450c17 is present exclusively in the UTCs, but is down-regulated when these cells differentiate into TGCs; P450arom level, on the other hand, increases as UTCs differentiate to TGCs (Schuler et al, 2008).…”
Section: Compartmentalization Of Progesterone Synthesismentioning
confidence: 99%
See 1 more Smart Citation